The association between quality system development stage and the implementation of process-level patient safety themes in Dutch hospitals: an observational study - Steffie M. van Schoten; Janneke Hoogervorst-Schilp; Peter P. Groenewegen; Peter Spreeuwenberg; Cordula Wagner (BMC, 2018)
Abstract Background Quality systems are believed to be positively related to quality and safety in healthcare. However, there is no convincing evidence for this relationship in the literature. This study aims to examine the association between the development stage of hospital quality systems and the implementation of patient safety themes at the process level. Methods This study combines data from a national survey on the development stage of quality systems in Dutch hospitals with results from an evaluation study of the Dutch Hospital Patient Safety Program. Data on the development stage of quality systems were collected in Dutch hospitals in 2011. A total of 73 quality coordinators completed a questionnaire (response rate 77%) covering five quality system domains: policy and strategy, human resource management, patient involvement, practice guidelines, and systematic quality improvement. Data were included on the implementation of five patient safety themes from the Dutch Hospital Safety Program. Process indicators for each theme were measured every four to six weeks, resulting in ten measurements in each hospital. Data were analyzed using multilevel analysis. Results The mean score for hospital quality system development was 2.30 (range 1 to 3). The mean scores for the various quality system domains ranged from 1.56 (Patient Involvement) to 2.66 (Human Resources Management). The mean percentages for the implementation of the patient safety themes ranged from 12% for the 'Pain' process indicator to 73% for execution of the 'Time-Out Procedure'. The intraclass correlation coefficients of the intercept-only model ranged between 11.6 and 51.6, which indicates large differences between hospitals in the implementation of the patient safety themes. Positive associations between quality system development stage and implementation of patient safety themes were found for four of the five patient safety themes, although they were not statistically significant. Conclusions This study found no association between the development stage of a hospital quality system and the implementation of patient level safety themes at the process level. This rejects the hypothesis that quality improvement is caused by a positive relationship between structure (the quality system) and processes (the safety program implementation), which in their turn mold the quality of care at the patient level.